Effects of applied potential on phosphine formation in synthetic wastewater treatment by Microbial Electrolysis Cell (MEC). (April 2017) - Liu, Wei; Niu, Xiaojun; Chen, Weiyi; An, Shaorong; Sheng, Hong
Abstract: Phosphine (PH3 ) emission from conventional biological wastewater treatment is very inefficient (ng-μg m −3 ). In this work, we investigated the feasibility of promoting PH3 formation from inorganic phosphorus (IP) or organic phosphorus (OP) containing synthetic wastewater treatment by Microbial Electrolysis Cell (MEC) for the first time. Positive effect of applied potential on PH3 production was observed after methanogens was inhibited. The highest production of PH3 (1103.10 ± 72.02 ng m −3 ) was obtained in IP-fed MEC operated at −0.6 V, which was about 5-fold and 2-fold compared to that in open circuit experiment and OP-fed MEC, respectively. Meanwhile, PH3 formation corresponded positively with current density and alkaline phosphatase activity. This result showed that suitable potential could enhance the activity of relevant enzymes and boost the biosynthesis of PH3 . Bacterial communities analysis based on high-throughput sequencing revealed that applied potential was conductive to the enrichment of phosphate-reducing organisms in contrast to the control test. These results provide a new idea for resource utilization of phosphorus in wastewater. Highlights: We evaluated the feasibility of promoting PH3 formation by MEC for the first time. Methanogen was one of the limit factors for PH3 production in MEC. PH3 production in MEC increased apparently than that in open circuit experience. PH3 production corresponded well with the change trends of current density and APA.